Optimization of genome engineering approaches with the CRISPR/Cas9 system. - Kai Li (Public Library of Science (PLoS), 2014)
Designer nucleases such as TALENS and Cas9 have opened new opportunities to scarlessly edit the mammalian genome. Here we explored several parameters that influence Cas9-mediated scarless genome editing efficiency in murine embryonic stem cells. Optimization of transfection conditions and enriching for transfected cells are critical for efficiently recovering modified clones. Paired gRNAs and wild-type Cas9 efficiently create programmed deletions, which facilitate identification of targeted clones, while paired gRNAs and the Cas9D10A nickase generated smaller targeted indels with lower chance of off-target mutagenesis. Genome editing is also useful for programmed introduction of exogenous DNA sequences at a target locus. Increasing the length of the homology arms of the homology-directed repair template strongly enhanced targeting efficiency, while increasing the length of the DNA insert reduced it. Together our data provide guidance on optimal design of scarless gene knockout, modification, or knock-in experiments using Cas9 nuclease.